Discriminative Monitoring of Seamless Rail Force by a High-Birefringence Effect-Based Fiber Optic Sensing Method - Zhou, Yin; Yan, Lianshan; Wang, Ping; Chen, Rong; Li, Zonglei; Ye, Jia; Pan, Wei; Luo, Bin (Frontiers in Physics, 2022)
Nowadays, China has developed over 38000-km high-speed railways (HSR). As one of the key elements in the HSR system, continuous welded rail (CWR) enables higher transportation efficiency, while demands for more robust inspection and maintenance techniques. The discrimination between longitudinal temperature force and longitudinal additional force is one of the main challenges in the rail health status evaluations. In this paper, the high-birefringence fiber Bragg grating (HB-FBG) is applied to reach the rail force discriminative measurement. By inscribing the Bragg grating on a high-birefringence fiber, two kinds of sensing modes can be generated and adopted to realize the discriminative measurement of longitudinal temperature force and longitudinal additional force. In the verification experiments, the longitudinal temperature and additional force are accurately measured with the error less than 1 kN. The accurate-measurement and easy-manufacture of the HB-fiber and HB-FBG make it possible to connect massive sensors in series to reach long-range monitoring of the rails on the land or cross-sea bridges.